Development of E-Module Guideline on Basic Physics Practicum for Science Process Skills in a Pandemic Period - Defianti, Aprina; Putri, Desy Hanisa; Rohayati, Siti; Herawati, Asmida; Chen, Li Yi (Journal of Natural Science and Integration, 2022)
The present study was carried out to produce a product in the form of e-module guidelines of basic physics practicum developed using the SIGIL application to practice students' science process skills during the covid-19 pandemic. This research-based paper was conducted through ADDIE model, which consisted of analysis, design, development, implementation, and evaluation stages. In the analysis phase, a needs analysis of questionnaire was conducted to determine the need for e-modules for practitioners and practicum assistants. During the design stage, a preliminary design is made in the form of the structure or content of the e-module, practicum titles, and their layout. Furthermore, in the development stage, the e-module has been developed using the SIGIL application by inserting a practical tutorial video based on a scientific approach and has been assessed with an average score of 3.82 considered Very Good. The implementation was carried out by giving the developed e-module to 20 students who took the basic physics practicum course. After using e-modules for 4 practicum titles, students are given a posttest of science process skills. Based on the posttest results, students received an average score of science process skills of 83.94 considered Skilled category. In addition to data on the score of science process skills, at this stage data on student responses to e-modules were also obtained using responses from questionnaires. The results disclosed that the developed e-module addressed a positive perception with an average response score of 89 considered Very Good. In the last evaluation stage, it was therefore argued that the e-module of basic physics practicum using SIGIL application was concluded appropriate to use on practicing students' science process skills during the Covid-19 pandemic.Keywords: e-module guidelines, basic physics practicum, science process skills.